2021
DOI: 10.1038/s41467-021-22175-3
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase-negative staphylococci release a purine analog that inhibits Staphylococcus aureus virulence

Abstract: Coagulase-negative staphylococci and Staphylococcus aureus colonize similar niches in mammals and conceivably compete for space and nutrients. Here, we report that a coagulase-negative staphylococcus, Staphylococcus chromogenes ATCC43764, synthesizes and secretes 6-thioguanine (6-TG), a purine analog that suppresses S. aureus growth by inhibiting de novo purine biosynthesis. We identify a 6-TG biosynthetic gene cluster in S. chromogenes and other coagulase-negative staphylococci including S. epidermidis, S. ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Arising from studies to uncover the therapeutic potential of bactericidal and bacteriostatic compounds produced by coagulase-negative staphylococci (CoNS) to compete with S. aureus in shared ecological niche, the Heinrich's group identified the CoNS-produced purine analogue 6-thioguanine (6-TG) and revealed its potential to both inhibit growth of S. aureus by interfering with ribosome biogenesis and downregulate agr-controlled virulence under purine limited growth conditions (67).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arising from studies to uncover the therapeutic potential of bactericidal and bacteriostatic compounds produced by coagulase-negative staphylococci (CoNS) to compete with S. aureus in shared ecological niche, the Heinrich's group identified the CoNS-produced purine analogue 6-thioguanine (6-TG) and revealed its potential to both inhibit growth of S. aureus by interfering with ribosome biogenesis and downregulate agr-controlled virulence under purine limited growth conditions (67).…”
Section: Discussionmentioning
confidence: 99%
“…Arising from studies to uncover the therapeutic potential of bactericidal and bacteriostatic compounds produced by coagulase-negative staphylococci (CoNS) to compete with S. aureus in shared ecological niche, the Heinrich’s group identified the CoNS-produced purine analogue 6-thioguanine (6-TG) and revealed its potential to both inhibit growth of S. aureus by interfering with ribosome biogenesis and downregulate agr -controlled virulence under purine limited growth conditions (67). Resistance to 6-TG can arise through mutations in PbuG (also named StgP, 6-thioguanine permease) and the Hpt hypoxanthine phosphoribosyltransferase (53), demonstrating that guanine/6-TG are transported and metabolised by PbuG/StgP and Hpt, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…are abundant colonizers of the normal microflora of humans and animals [ 1 ]. Despite living in commensalism with the host, staphylococci, in particular, Staphylococcus aureus , can cause a wide spectrum of infections [ 2 ]. The Staphylococcus genus comprises the coagulase-negative staphylococci (CoNS) and coagulase-positive staphylococci (CoPS) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent studies have shown that CoNS have an increasing clinical impact and can act as opportunistic pathogens, particularly in immunocompromised patients [ 1 , 4 , 5 , 6 ]. Staphylococci can easily acquire antimicrobial resistance genes, preventing the treatment of some infections [ 2 ]. Over the last few decades, methicillin-resistant S. aureus (MRSA) have been a leading cause of nosocomial infections and an emergent zoonotic pathogen [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus lugdunensis strains produce lugdunin, a novel thiazolidine-containing cyclic peptide antibiotic that prohibits colonization by S. aureus [ 32 ]. Quite a number of CoNS produce 6-thioguanine (6-TG), a purine analog that suppresses S. aureus growth by inhibiting de novo purine biosynthesis and is also effective in wound healing [ 33 ]. Other CoNS produce lantibiotics such as epidermin and gallidermin, which inhibit cell wall biosynthesis and have broad-spectrum activity against Gram-positive pathogens [ 34 , 35 ], or antimicrobial peptides (AMPs) that selectively kill S. aureus and synergize with the human AMP LL-37 [ 36 ].…”
Section: Positive Effect Of Some Commensals and Probiotics On Wound Healingmentioning
confidence: 99%